Import risks of agricultural products in foreign trade - Lina Baranauskaitė; Daiva Jurevičienė (Economies, 2021)
This paper aims to identify the main risk groups according to their significance on imports of agricultural products. After analysis of the scientific literature, eight groups of risks associated with agricultural products import were determined: supply risks, demand risks, production risks, management plus operational risks, logistical plus infrastructural risks, political risks, policy plus regulatory risks and financial risks. In order to assess the importance of all import risk groups, three Multicriteria decision support methods (MCDM)-SAW, TOPSIS and Geometric means-for expert evaluation are used. The article introduces a new import risks assessment framework CIRA (Country's Imports Risk Assessment) contributing to the systematic approach of a country's international trade risks management. The results order risk groups according to their importance in the following order: production (the most crucial risk group), logistical plus infrastructural, financial, management plus operational, political, supply, policy plus regulatory and demand risks.
Keywords: 330; import risks; agricultural products; agro-trade; food import; SAW; TOPSIS; geometric means